A hydrodynamic AFM flow cell for the quantitative measurement of interfacial kinetics - Coles, B; Compton, R; Booth, J; Hong, Q; Sanders, G (1997)
A novel liquid flow cell is developed which allows atomic force microscopy images to be obtained under defined and modelled hydrodynamic flow conditions, enabling measured reaction fluxes to be compared with those calculated from proposed heterogeneous reaction mechanisms.